Syiir Tanpo Waton and The Spirit of Indonesian Religious Moderation - Luthfi Rahman; Efri Arsyad Rizal; Azma Zuhayda Arsyada (Jurnal Penelitian, 2021)
This research is aimed to dismantle and to reveal the religious moderation values from a local legacy of a Muslim cleric/kyaiâ€™s reflective thought written in a Javanese-Arabic poem (syiir) â€œTanpo Watonâ€ authored by KH. Muhammad Nizam As-Shofa, a local kyai and a spiritual master of the Naqsyabandiyyah Kholidiyyah sufi order. What remains interesting in this syiir is that it has been inaugurated by the national figure of pluralism as well as the fourth president of Indonesia, KH. Abdurrahman Wahid (Gus Dur) through his popular melodious chanting. This is a qualitative-descriptive research. Data collection in this study uses documentation, with a content and discourse analysis technique through the lens of religious moderation concept as the currently Indonesian grand narrative campaign for religious harmony. The analysis then entails the production of data in which there are textual and contextual meaning implied within the syiir which emphasizes how important it is to stick with the values of religious moderation for building Indonesian harmony and strengthening national unity within diversity. The religious moderation narrative within the syiir indeed embeds the values of nationalism, tolerance, non-violence and local wisdom respect. Such values are among the pivotal elements to teach and disseminate towards Indonesian generations for the sake of Indonesian harmony.